Hydrogen production by high temperature electrolysis coupled with an EPR, SFR or HTR: techno-economic study and coupling possibilities. (14th July 2008) - Rivera-Tinoco, Rodrigo; Mansilla, Christine; Bouallou, Chakib; Werkoff, Francois
Hydrogen production by high temperature electrolysis coupled with three nuclear reactors (the European pressurised reactor, the sodium-cooled fast reactor and the very high temperature reactor) was studied in terms of perspectives and hydrogen production costs. Firstly, we present the features of producing water steam by using the three nuclear reactors. Secondly, we present the hydrogen production cost for the HTE process coupled with each type of nuclear reactor. These costs are optimal values of the hydrogen production cost for the mentioned couplings and they were estimated by using a genetic algorithm procedure. High potentiality for these HTE couplings was assessed and contrary to steam source temperatures, the electricity price appeared to be a key parameter for low hydrogen production costs.